Are There Differences in the Health Outcomes of Mothers in Europe and East-Asia? A Cross-Cultural Health Survey. (27th November 2014) - Mautner, Eva; Ashida, Chie; Greimel, Elfriede; Lang, Uwe; Kolman, Christina; Alton, Daniela; Inoue, Wataru
Abstract : The aim of the current study was to investigate differences in quality of life outcomes and depression of mothers in East-Asia and Central Europe. 170 women in Japan and 226 women in Austria with children between 3 and 5 answered the same cross-culturally validated questionnaires. The Quality of Life Questionnaire from the WHO (WHOQOL-Bref), the Patient Health Questionnaire (PHQ-2), the Sense of Coherence Scale (SOC-13), a Social Support Scale (MSPSS), and questions on gender orientation were used. In all dimensions of QOL (physical, psychological, social, and environmental) Japanese women had lower QOL scores compared to Austrian mothers (P < 001 ). Seven percent of women in both countries experienced major depression. In both countries sense of coherence, experienced stress level, satisfaction with income, social support, and gender roles had an influence on QOL and depressive symptoms. Mothers in Japan consider life events less comprehensible, manageable, and meaningful and experience less support. Consequently, creating an environment where fathers could be more involved in child rearing and mothers have more opportunities to choose between life styles and working and social environments would improve QOL not only in Japanese mothers but also in other countries all over the world.